Building the Missing Bridge: Teenagers' Need for Parental Support in Teenager Pregnancy Prevention - Laily Mualifah; Siti Maryati; Budi Punjastuti (Indonesian Journal of Global Health Research, 2026)
Adolescence is a transitional period from childhood to adulthood, characterised by high levels of curiosity that require positive guidance. Teenage pregnancy is a significant public health issue in many developing countries, including Indonesia. Teenage pregnancy can have various impacts on both the mother and the baby. Physically, adolescents are not ready to conceive or give birth, which makes them vulnerable to complications that can be fatal. This study aimed to explore the need for parental support in preventing teenage pregnancy among adolescents. A qualitative, phenomenological approach was used, involving three pregnant adolescents under the age of 18 in Bantul, Special Region of Yogyakarta. Data were collected through in-depth interviews, transcribed, coded and analysed to identify patterns in the participants' experiences and perceptions. The results showed that adolescents need support from their parents in the form of emotional attention, intimacy, open communication, a harmonious home environment and guidance on reproductive health. Such support enables adolescents to feel safe and comfortable discussing personal issues, thereby reducing the risk of risky sexual behaviour and unwanted pregnancies. This study emphasises the importance of building “bridges” of communication and support between adolescents and parents as a strategy for preventing teenage pregnancy.